ANALISIS PROFITABILITAS USAHA MIKRO INDUSTRI JENIS MAKANAN LAUT (SEAFOOD) DI KECAMATAN TAMPAN KOTA PEKANBARU - suryati suryati; Suarman Suarman; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT Industrial seafood is one of the micro-enterprises that are currently in great demand by most people in Pekanbaru . Increased public interest in seafood will be potentially huge market opportunity to earn huge profits . When going to open a seafood industry means one must consider how the profitability of the business 's ability to generate earnings that will be a picture of the effectiveness of the business . The purpose of this study was to determine the level of profitability of microenterprise industry types seafood. The population in this study were all kinds of micro-businesses of seafood industry in Pekanbaru listed in the Department of Cooperatives and UMKM in Pekanbaru as many as 44 population . This study used purposive sampling method with the following criteria : 1 ) the type of industry Micro seafood which carries on business in Pekanbaru . 2 ) Micro-businesses in the seafood industry types with financial records in running their business . Techniques of data collection was through interviews . Analysis using averaging techniques and technical profitability in net income . The results showed that the average net profit industry types seafood industry as a whole amounted to Rp 5,369,185 , - . And the highest profitability in the amount of 48.36 % so that capital can be returned within a period of 3 months , and the profitability of the other respondents , namely a maximum of 19.00 % and can restore the capital within a period of 6 months .Keywords : Profitability , Micro, Micro Type Seafood Industry